Wastewater Management in Hanoi: The Possibility of Using a Soft Path Approach - Trang, Nguyen Thi Thu; Walsh, John; Robert McClelland (Journal of Social and Development Sciences, 2022)
Hanoi is known as the City of Lakes because there are some one hundred natural or manmade watercourses within its territory. However, in common with all of Vietnam, more than 60% of the city’s water resources derive from beyond the country’s borders. Much of that water is polluted, both within Hanoi and downstream because wastewater is discharged directly into the Nhue and Day rivers via the Nhat Tuu and Ba sewers, among other channels. International attempts to revive the To Lich River in the city, notorious for its black color and unwholesome smell, have proved to have only limited success. There is some scope for new materials to improve filtration effects and experiments in this area continue. Rapid urbanization in Hanoi has been intensified by the sudden decision to increase the city’s size so that it became comparable to the southern capital of Ho Chi Minh City. This has led to large areas of industrial land being incorporated into municipal water management systems. One possible means of relieving the pressure on these systems would be to employ approaches derived from the soft path of water management. To date, most scientific investigation of these issues depends almost entirely on technocratic approaches to water management issues and the attempt to force technical solutions to deal with social issues. Consequently, this paper investigates the possibility of understanding how Hanoi residents interact with current wastewater management approaches and how their needs might be better met in the future.